Factibilidad del sistema fotovoltaico para suministrar energía a una estación de carga de bicicletas eléctricas en la ciudad de Loja - Valarezo Borrero, Jaime Sebastián (2024)
The present research project has focused on the design of a solar-powered electric station to supply energy to electric bicycles in strategic locations in the city of Loja. The development of the project began with the collection of data regarding the technical characteristics of models of electric bicycles and scooters most used in the city of Loja, with this information the daily energy demand was determined. Then, the solar radiation data of Loja was investigated. The data was obtained from the Solar Potential of the Southern Region of the Country project developed by the National University of Loja, with an average value of 3.64 kWh/m²/ day. The information gathered was used to size the charging system, and the photovoltaic generation system, which has a power of 2120 W, requires 8 solar panels of 265 W/24 V, 4 batteries of 200 Ah/24 V, 1 inverter of 3 kW 24/120 V and a charge controller of 65 A MPPT. The design of the proposed prototype consists of 3 charging units, the outlets are at 120 Volts to connect the portable charger of the mobile units. Plans and exploded views of the prototype were prepared in 2D and 3D. The electric station consists of a 3.4m long and 3.5 m wide cover, and the structure it is 3.20 m high. The proposed locations for the implementation of the cargo units are based on the layout of the bicycle lanes in the city of Loja and the availability of space. Five suitable locations are considered: Jipiro Park, Bolívar Park, Line Park La Tebaida, Universidad Nacional de Loja, and Reina del Cisne Stadium. Keywords: Electric power station, Electric bicycle, photovoltaic, renewable solar radiation, single radiation.